Антроподжерельна невербальна інформація в кримінальному провадженні: криміналістичні засади - Ващук, Олеся Петрівна; Ващук, Олеся Петровна; Vashchuk, Olesya P. (My University, 2018)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.09 - кримінальний процес та криміналістика; судова експертиза; оперативно-розшукова діяльність. - Національний університет «Одеська юридична академія». Одеса, 2018. Дисертація є першою в Україні кваліфікаційною науковою працею, у якій запропоновано комплексну криміналістичну концепцію сприйняття та використання антроподжерельної невербальної інформації в кримінальному провадженні. Визначено ступінь наукової розробленості проблеми дослідження та застосування невербальної інформації в криміналістиці. Охарактеризовано загальні наукові положення сприйняття та використання невербальної інформації в кримінальному провадженні. Визначено поняття та джерела антроподжерельної невербальної інформації в кримінальному провадженні та здійснено її класифікацію. Охарактеризовано значення антроподжерельної невербальної інформації в кримінальному провадженні. Сформульовано принципи використання антроподжерельної невербальної інформації в кримінальному провадженні. Диференційовано методи і засоби дослідження антроподжерельної невербальної інформації в кримінальному провадженні. Охарактеризовано традиційні методи і засоби дослідження антроподжерельної невербальної інформації в кримінальному провадженні та запропоновано інноваційні методи її дослідження. Визначено загальні положення тактики використання антроподжерельної невербальної інформації на досудовому розслідуванні. Окреслено специфіку сприйняття і використання антроподжерельної невербальної інформації під час проведення допиту. Сформульовано практичні рекомендації щодо сприйняття і використання антроподжерельної невербальної інформації під час проведення обшуку. Визначено загальні положення тактики використання антроподжерельної невербальної інформації в судовому провадженні й запропоновано тактичні рекомендації сприйняття та її використання в судовому провадженні.

Диссертация на соискание научной степени доктора юридических наук по специальности 12.00.09 - уголовный процесс и криминалистика; судебная экспертиза; оперативно-розыскная деятельность. - Национальный университет «Одесская юридическая академия». Одесса, 2018. Диссертация является первой в Украине квалификационной научной работой, в которой предложена комплексная криминалистическая концепция восприятия и использования антропогенной невербальной информации в уголовном производстве. Определена степень научной разработанности проблемы исследования и использования невербальной информации в криминалистике. Охарактеризованы общие научные положения восприятия и использования невербальной информации в уголовном производстве. Определено понятие и источники антропогенной невербальной информации в уголовном производстве и осуществлена ее классификация. Охарактеризовано значение антропогенной невербальной информации в уголовном производстве. Сформулированы принципы использования антропогенной невербальной информации в уголовном производстве. Дифференцированы методы и средства исследования антропогенной невербальной информации в уголовном производстве. Охарактеризованы традиционные методы и средства исследования антропогенной невербальной информации в уголовном производстве и предложены инновационные методы ее исследования. Определены общие положения тактики использования антропогенной невербальной информации на досудебном расследовании. Определена специфика восприятия и использования антропогенной невербальной информации при проведении допроса. Сформулированы практические рекомендации по восприятию и использованию антропогенной невербальной информации при проведении обыска. Определены общие положения тактики использования антропогенной невербальной информации в судебном производстве и предложены тактические рекомендации восприятия и ее использования в судебном производстве.

The Thesis for the Degree of Doctor of Law in Specialty 12.00.09 - criminal procedure and criminalistics; court examination; operative-investigative action. - National University «Odesa Law Academy». Odesa, 2018. The thesis is the first qualification scientific work in Ukraine, which offers a comprehensive criminalistical concept of the perception and use of anthropogenic nonverbal information in criminal proceedings. The degree of scientific development of the problem of research and use of nonverbal information in criminalistics has been determined. The main stages of scientific development of nonverbal information are singled out. The general scientific positions on perception and use of nonverbal information in criminal proceedings are characterized. The necessity to integrate the provisions of anthropogenic nonverbal information as a complex dynamic system into the theory of criminalistics, which includes the practice of criminal proceedings and criminalistical recommendations, aimed at improving this practice, is substantiated. The concept of perception and use of anthropogenic nonverbal information is developed. The concept and sources of anthropogenic nonverbal information in criminal proceedings are defined and its classification is carried out. The scientific category «anthropogenic nonverbal information» was introduced into the doctrinal circulation, which is proposed to be defined as information of a personality about psychological, physiological, social and other properties and signs of state and speech (or manifestations of non-linguistic communication) of persons involved in criminal proceedings, with the aim of clarification of their relation to the investigated event. The types of anthropogenic nonverbal information in criminal proceedings are characterized, in the basis of classification of which are two classes of manifestation of nonverbal information: kinesic (gestural, mimic, pantomimetic, tactile, myremic manifestations) and paralinguistic (fonetic, respiratory manifestations). The functions of anthropogenic nonverbal information in criminal proceedings are defined. The significance of anthropogenic nonverbal information in criminal proceedings is described. Nonverbal information is defined as a kind of criminalistical information and its significance in criminal proceedings is disclosed. The principles of use of anthropogenic nonverbal information in criminal proceedings (unity of activity and consciousness, objectivity, taking into account the relationship of physiology and psychology, historical approach, twodimensional manifestations) are formulated. Methods and means of research of anthropogenic nonverbal information in criminal proceedings are differentiated into traditional and innovative. Traditional methods and means of research of anthropogenic nonverbal information in criminal proceedings (sensory-rational, technical methods and means of research, mixed) and innovative methods of research (verification, validation, verbalization, psychophysiological method) are described. The general provisions of the tactics of use of anthropogenic nonverbal information on pre-trial investigation are defined: circulating in criminal proceedings at the stages of pre-trial investigation and court proceedings; subjects of perception and use are all participants in criminal proceedings; primarily non-procedural form of implementation; the focus on information provision for pre-trial investigation and court proceedings. The specificity of the perception and use of anthropogenic nonverbal information during the interrogation is outlined. The conceptual ideas of the individual approach to the tactics of use the provisions of nonverbal information, development of the direction of negotiation tactics as a constituent of criminalistical provision to achieve procedural compromise, and verification as the first principle of the approach to determining the degree of reliability of the information received, are improved. Practical recommendations for the perception and use of anthropogenic nonverbal information during the search and propositions on the perception and use of nonverbal manifestations of the participant in criminal proceedings are formulated, which supplement the contents of the available criminalistics recommendations that reveal techniques for detecting lies, establishing contact, interaction, obtaining and studying data etc. The general provisions of the tactics of use of anthropogenic nonverbal information in the court proceedings are determined and tactical recommendations of perception and its use in court proceedings are proposed. The nature, limits and possibilities of use the provisions of anthropogenic nonverbal information in criminal proceedings are revealed, traditional and new forms of application of such knowledge are highlighted.
дис. ... д.ю.н. : 12.00.09
Ващук О.П. Антроподжерельна невербальна інформація в кримінальному провадженні: криміналістичні засади: дис. ... доктора юрид. наук: 12.00.09 / Ващук Олеся Петрівна. - Одеса, 2018. - 506 с.
Keywords: невербальна інформація; антроподжерельна невербальна інформація; метод дослідження; верифікація; валідація; принцип використання; тактика використання; невербальная информация; антропогенная невербальная информация; метод исследования; верификация; валидация; принцип использования; тактика использования; nonverbal information; anthropogenic nonverbal information; research method; verification; validation; principle of use; tactics of use